2013
DOI: 10.1111/jgs.12530
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data from an Advanced Dementia Consult Service: Integrating Research, Education, and Clinical Expertise

Abstract: Hospitalized patients with advanced dementia often receive care that is of limited clinical benefit and inconsistent with preferences. We designed an Advanced Dementia Consult Service and conducted a pre and post pilot study to evaluate it in a Boston hospital. Consults were conducted by geriatricians and palliative care nurse practitioner. They consisted of structured consultation, counseling and provision of an information booklet to the family, and post-discharge follow-up with the family and primary care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(68 citation statements)
references
References 20 publications
0
68
0
Order By: Relevance
“…In the months following palliative care consults, patients and family caregivers reported that they continued to require information about advanced illness. In contrast, other researchers found that engaging patients and family caregivers in ongoing communication, education, and advance-care planning during and after discharge may result in clearer expectations and care aligned with preferences (Catic et al, 2013; Gerrard et al, 2011). …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In the months following palliative care consults, patients and family caregivers reported that they continued to require information about advanced illness. In contrast, other researchers found that engaging patients and family caregivers in ongoing communication, education, and advance-care planning during and after discharge may result in clearer expectations and care aligned with preferences (Catic et al, 2013; Gerrard et al, 2011). …”
Section: Resultsmentioning
confidence: 89%
“…Methodological approaches varied, though most studies were pilot work or descriptive (Benzar, Hansen, Kneitel, & Fromme, 2011; Blackford & Street, 2001; Catic et al, 2013; Thon Aamodt, Lie, & Helleso, 2013). Three studies were longitudinal over a one- to two-year period (Fromme et al, 2006; Kötzsch, Stiel, Heckel, Ostgathe, & Klein, 2014), including one ethnography (Tallman, Greenwald, Reidenouer, & Pantel, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations